TIME SERIES ANALYSIS USING COPULA GAUSS AND AR(1)-N.GARCH(1,1) - Caraka, Rezzy Eko; Yasin, Hasbi; Sugiarto, Wawan; Ismail, Kadi Mey (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
In this case, the Gaussian Copula is used to connect the data that correlates with the time and with other data sets. Most often, practitioners rely only on the linear correlation to describe the degree of dependence between two or more variables; an approach that can lead to quite misleading conclusions as this measure is only capable of capturing linear relationships. Correlation doesnâ€™t mean causation, prediction using Copula is built on three things that the marginal distribution function, the kernel function, and the function of the Copula. Gaussian Copula involves the covariance matrix are approximated by using kernel functions. Kernel acts as the correlation between the approach of the data values that have the same characteristics. In this case, the characteristics used is the time. The advantage of the kernel function is able to calculate the correlation between random variables that have a realization using data characteristics. The advantage of using the kernel based Copula able to capture the dependencies between data and process data that have the same characteristics with time. Another benefit is that it allows a sequence of random variables have a joint distribution function so that the conditional probability of the prediction can be calculated.Â Keywords: Binding, Copula, GARCH, Gauss, Time Series